2021
DOI: 10.1002/agg2.20162
|View full text |Cite
|
Sign up to set email alerts
|

Grain sorghum production: Influence of planting date, hybrid selection, and insecticide application

Abstract: Grain sorghum [Sorghum bicolor (L.) Moench] has been a valuable crop for the southern Great Plains due to its ability to overcome the high temperatures and sporadic rain events common in the region. Optimizing production practices has always been critical for grain sorghum to overcome these environmental challenges. In response to sugarcane aphids (SCA), a detrimental pest in grain sorghum production, common agronomic management practices rapidly shifted with no regard to how such changes would affect overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Higher yields in early spring resulted from the synchronization of planting dates with the onset of precipitation, which increased the frequency of WW environments ( Supplementary Figure S3 ). Likewise, simulation and field studies demonstrated yield gains of up to 11% in seasons with higher water availability ( Francis et al., 1986 ; Carcedo et al., 2021 ; Zander et al., 2021 )…”
Section: Discussionmentioning
confidence: 96%
“…Higher yields in early spring resulted from the synchronization of planting dates with the onset of precipitation, which increased the frequency of WW environments ( Supplementary Figure S3 ). Likewise, simulation and field studies demonstrated yield gains of up to 11% in seasons with higher water availability ( Francis et al., 1986 ; Carcedo et al., 2021 ; Zander et al., 2021 )…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, in areas such as Zhangjiakou, which has a relatively longer frost-free period, proper delayed sowing may be suitable to obtain a higher yield if sorghum can get mature. However, planting date had a significant effect on early-season seedling emergence and varied between years ( Radford and Henzell,1990 ; Razmi et al., 2013 ; Zander et al., 2021 ), climatic characteristics of different years, cold tolerance of variety should be considered for setting a proper early sowing date.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments, conducted at Lahoma and Efaw of Oklahoma, showed that planting date significantly affected grain sorghum yield. Optimum yields were found when planting in April or May, depending on year, and cooler soil temperatures can limit yield when grain sorghum is planted too early (Zander et al, 2021). However, research in Missouri indicated that planting date had a small and inconsistent effect on grain sorghum yield, and a rather wide planting date window was found (Conley and Wiebold, 2003) .…”
Section: Introductionmentioning
confidence: 99%
“…A large body of literature found important differences between sorghum varieties in terms of yield, nutritional content, and tolerance to climate risks (Amare et al, 2015;Ogbaga et al, 2016;Assefa et al, 2020;Tasie and Gebreyes, 2020;Wendmu et al, 2022). Similarly, agronomic practices such as tillage, plant density, and sowing date, among others, are found to widely impact sorghum yield (Conley and Wiebold, 2003;Ajaj et al, 2021;Carcedo et al, 2021;Zander et al, 2021;Gao et al, 2022;Naoura et al, 2023), indicating that adopting best agronomic practices is an indispensable factor for any program that aims to improve crop productivity and build climate resilience.…”
Section: Improved Varieties and Better Agronomic Practicesmentioning
confidence: 99%